2010
DOI: 10.1103/physrevb.81.033105
|View full text |Cite
|
Sign up to set email alerts
|

Third element effect in the surface zone of Fe-Cr-Al alloys

Abstract: The third element effect to improve the high temperature corrosion resistance of the low-Al Fe-Cr-Al alloys is suggested to involve a mechanism that boosts the recovering of the Al concentration to the required level in the Al-depleted zone beneath the oxide layer. We propose that the key factor in this mechanism is the coexistent Cr depletion that helps to maintain a sufficient Al content in the depleted zone. Several previous experiments related to our study support that conditions for such a mechanism to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Our previous work [18] suggested that the newly formed IMCs rich in Fe are based on an Al 3.2 Fe-type structure (65 wt % Al, 35 wt % Fe) and that the newly formed IMC rich in Cr could be the non-stoichiometric Al 45 Cr 7 -type structure (78 wt % Al, 11 wt % Cr, 9 wt % Fe, 2 wt % Ti). The phase separation tendencies of Fe and Cr in Fe-Cr, Fe-Cr-Al, and Fe-Cr-Al-Ti alloys at elevated temperatures [27][28][29] or under irradiation [30,31] have been previously reported, resulting in similar elemental separation. IMC phases with larger sizes (several microns) remain rich in both Fe and Cr ( Figure 5(c1-c5,d1-d5)) while maintaining compositions similar to the starting powders.…”
Section: Microstructural Investigationsupporting
confidence: 66%
“…Our previous work [18] suggested that the newly formed IMCs rich in Fe are based on an Al 3.2 Fe-type structure (65 wt % Al, 35 wt % Fe) and that the newly formed IMC rich in Cr could be the non-stoichiometric Al 45 Cr 7 -type structure (78 wt % Al, 11 wt % Cr, 9 wt % Fe, 2 wt % Ti). The phase separation tendencies of Fe and Cr in Fe-Cr, Fe-Cr-Al, and Fe-Cr-Al-Ti alloys at elevated temperatures [27][28][29] or under irradiation [30,31] have been previously reported, resulting in similar elemental separation. IMC phases with larger sizes (several microns) remain rich in both Fe and Cr ( Figure 5(c1-c5,d1-d5)) while maintaining compositions similar to the starting powders.…”
Section: Microstructural Investigationsupporting
confidence: 66%
“…Many alloys or alloy coatings for high-temperature applications are based on iron, nickel and/or cobalt and rely on the establishment of Cr 2 O 3 , A1 2 O 3 or SiO 2 healing layers for protection against oxidation. These oxides are thermodynamically very stable with respect to the metal and have high melting points; transport processes through the scales are generally slow [54][55][56][57]. Actually, in the various methods for CVD diamond films on steel substrates, the Al, Si, Cr elements have already been used by some researchers.…”
Section: Methods Similar To Hot Corrosion Resistance Such As Aluminimentioning
confidence: 99%
“…Due to the oxidation induced variations in local atomic concentrations the relative balance between the chemical potentials in bulk and at the surface region is disturbed inducing biased driving force for atomic diffusion. Theoretical investigations show that Cr has a potential to activate a kind of Al-pump from the bulk to the surface [24]. For instance, total energy calculations combined with thermodynamic optimization show that at 900 K the Al concentration at the surface of Fe5Al is increased from 63 to 72 (81) at.% when 5 (10) at.% Cr is added to the alloy [17].…”
Section: Oxidation Analyzed With Calculated Chemical Potentialsmentioning
confidence: 99%
“…Then, by successive sputtering and Auger electron spectroscopy (AES) measurements of the oxidized surfaces, combined with theoretical considerations, it was possible to construct a time reversed picture of the oxidation. Using this picture it was possible to reconstruct a model for possible oxidation related atomic processes within the metal-oxide interface region [17,24].…”
Section: Introductionmentioning
confidence: 99%